2018
DOI: 10.1007/s00417-018-3992-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between wide-angle OCT angiography and ultra-wide field fluorescein angiography for detecting non-perfusion areas and retinal neovascularization in eyes with diabetic retinopathy

Abstract: The wide-angle OCTA seems to be clinically useful for the detection of NPAs or NV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 10 publications
4
94
0
1
Order By: Relevance
“…Sawada and associates reported the usefulness of OCTA with five 12 × 12‐mm images, which was similar to the current study, and detected retinal nonperfusion or neovascularization in patients with DR (Sawada et al. ). The current study extended the field of view to 12 × 12 mm and the additional OCTA images at four fixation positions of the visual field (inferonasal, superonasal, inferotemporal, and superotemporal), which made possible the approximately 2.4‐time enlargement of the single‐centre OCTA field of view.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Sawada and associates reported the usefulness of OCTA with five 12 × 12‐mm images, which was similar to the current study, and detected retinal nonperfusion or neovascularization in patients with DR (Sawada et al. ). The current study extended the field of view to 12 × 12 mm and the additional OCTA images at four fixation positions of the visual field (inferonasal, superonasal, inferotemporal, and superotemporal), which made possible the approximately 2.4‐time enlargement of the single‐centre OCTA field of view.…”
Section: Discussionsupporting
confidence: 89%
“…The width of the field of view of the panoramic OCTA image was approximately nine times that of the 6 × 6‐mm conventional OCTA images (Sawada et al. ). The current study was the first to quantify wide‐field OCTA images with skeletonized VL density and showed that the VL was correlated with the area of retinal nonperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Additionally, wide-field OCTA has high sensitivity and specificity for the detection of the NPA and NVs. 14,[21][22][23] In our study, OCTA clearly visualized NV, IRMAs, and the NPA without being affected by PC scars. Moreover, it was possible to distinguish NVs from IRMAs by confirming B-scans.…”
Section: Discussionsupporting
confidence: 64%
“…Montaged images were generated from these five images using built-in software on the instrument. 15 En face OCTA images of the full retinal thickness, generated by automatically segmenting the inner limiting membrane to 70 lm above the retinal pigment epithelium, were used for analyses. OCTA imaging was performed by trained ophthalmic photographers who repeated image acquisitions several times if necessary to ensure that images with good OCT signal penetration (signal strength þ7) and minimal motion artifacts were obtained.…”
Section: Octa Imagingmentioning
confidence: 99%